Pociąg jako tło i konstrukcja wydarzeń w powieściach Antonii Susan Byatt - Buda, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The materials used to analyse the motif of a train are two postmodern novels by English writer Antonia Susan Byatt: The Shadow of the Sun and Possession. For the writer, the train becomes the place of realisation of the unchangeable and static chronotope, whose characteristic feature is the time hiatus. These novels are analysed according to the following categorisation:
Keywords: pociągi; podróż; czasoprzestrzeń; intertekstualność; powieść autotematyczna; trains; travel; chronotope; intertextuality; surfiction